HUBUNGAN ANTARA DUA METODE SORTASI DENGAN VIABILITAS DAN VIGOR BENIH KACANG TANAH (Arachis hypogaea L.) SERTA APLIKASINYA UNTUK PENDUGAAN KETAHANAN SALINITAS - Sabaruddin Zakaria (Jurnal Floratek, 2006)
Relationship Between Two Sortation Method with Peanut Seed (Arachis hypogaea L.)  Viability and Vigor and Its Application for Salinity Resistance Approximation Sabaruddin Zakaria dan Cut Meutia Fitriani ABSTRACT The research has been made to explain the relationship between two-sortation methods with peanut seed (Arachis hypogaea, L.) viability and vigor and its application for salinity resistance appraisal. Completely Randomized Design with Factorial type 3 x 3 and 3 repetitions was used to analyze the effect of sortation method. The parameters used in this research were seed growth potential, germination ability, growth velocity and T50. The second research for salinity resistance was using Completely Randomized Design with Factorial type 2x4 and 3 repetitions. The parameters used in this research were seed vigor, growth velocity and T50. The research results showed that sortation method did not have significant difference on the peanut seed viability. Seed sortation by using 1.5 % NaCl solution could be used as one alternative for sortation of peanut seed. However, the sortation by using 3.0 % NaCl solution caused negative effect on the viability and vigor of peanut seed. Salinity factors gave high significant difference on the viability of seed. The highest seed viability was found without NaCl treatment (control). Relationship between salinity and seed viability was linear negative, meanings that higher salinity cause lower seed viability.